Ultrasensitive Electrochemical DNA Biosensor Fabrication by Coupling an Integral Multifunctional Zirconia-Reduced Graphene Oxide-Thionine Nanocomposite and Exonuclease I-Assisted Cleavage - Chen, Zhiqiang; Liu, Xueqian; Liu, Dengren; Li, Fang; Wang, Li; Liu, Shufeng (Frontiers in Chemistry, 2020)
In this work, a simple but sensitive electrochemical DNA biosensor for nucleic acid detection was developed by taking advantages of the exonuclease (Exo) I-assisted cleavage for background reduction, and zirconia-reduced graphene oxide-thionine (ZrO2-rGO-Thi) nanocomposite for the integral DNA recognition, signal amplification and reporting. The ZrO2-rGO nanocomposite was obtained by a one-step hydrothermal synthesis method. Then, the thionine was adsorbed onto the rGO surface via π-π stacking as an excellent electrochemical probe. The biosensor fabrication is of very simplicity with the probe DNA immobilization and hybridization recognition with target nucleic acid. Then, the ZrO2-rGO-Thi nanocomposite was captured onto electrode via the multicoordinative interaction of ZrO2 with the phosphate group on the DNA skeleton. The adsorbed abundant thionine molecules onto ZrO2-rGO nanocomposite facilitated an amplified electrochemical response related with target DNA. Since the interaction of ZrO2-rGO-Thi nanocomposite with probe DNA immobilized electrode may also occur, an Exo I-assisted cleavage was combined to remove the unhybridized probe DNA for background reduction. With current proposed strategy, target DNA related with P53 gene could be sensitively assayed with a wide linear detection range from 100 fM to 10 nM and an attractive low detection limit of 24 fM. Also, the developed DNA biosensor could differentiate the mismatched targets from complementary target DNA. Therefore, it offers a simple but effective biosensor fabrication strategy and is anticipated to show the potential for the applications in bioanalysis and medical diagnosis.